Thermal conductivity effect on thermophoresis of charged spheroidal colloids in aqueous media - Yang, Mingyuan (2023)
Thermophoresis of spheroidal colloids in aqueous media under the thermal conductivity effect is analyzed. The thermophoretic velocity and the thermodiffusion coefficient of spheroidal colloids have been formulated for extremely thin electric double layer (EDL) cases. Furthermore, a numerical thermophoretic model is built for arbitrary EDL thickness cases. The parametric studies show that the thermal conductivity mismatch of particle and liquid gives rise to a nonlinear temperature region around the spheroid, with the thickness close to the minor semiaxis. When the EDL region is thin relative to such nonlinear temperature region, the thermal conductivity effect on the thermophoresis of spheroidal colloids is significant, which strongly depends on the ratio of the minor semiaxis to the EDL thickness, the thermal conductivity ratio of particle to liquid, and the particle aspect ratio. Finally, to estimate the thermodiffusion coefficient of spheroidal colloids with arbitrary thermal conductivity, electrolyte concentration, and particle shape, the average dimensionless axial temperature gradient on the spheroidal equator plane in the EDL region is proposed.